Element-based ecological and human health risk assessment in a lagoon system in a densely populated basin - Aykir Dilek; Fural Şakir; Kükrer Serkan; Mutlu Yunus Emre (Oceanological and Hydrobiological Studies)
This study analysed the ecological deterioration and health risk in sediment samples taken from Dalyan and Poyraz Lagoons in the Karacabey floodplain of Turkey, which is under pressure from agriculture, industry and settlement activities. Multi-element analyses were performed with ICP-MS on the surface and core sediment samples from the lagoons. Total organic carbon, chlorophyll degradation products and carbonate analyses were performed to determine the transport and illuviation dynamics of the elements. While Pb and Zn showed moderate enrichment at some sampling points, no enrichment of the other elements was detected. According to ecological risk analysis data, Cd and Hg posed a moderate ecological risk at some sampling points. The modified hazard quotient data indicated very high contamination of Ni, a high level of As contamination and significant Cr contamination. A carcinogenic health risk was detected from Ni, Cr and As due to the lithological characteristics of the basin. It was concluded that the lithological characteristics, the agricultural and mining activities carried out in the Susurluk Basin – which is drained by Koca Stream – and domestic and industrial waste contributed to the higher element concentrations in the Karacabey floodplain.